Pengaruh Experiential Marketing Dan Kualitas Layanan Terhadap Kepuasan Pelanggan (Studi Pada Pelanggan Dapur Ayek Bengkulu) - Fadhlurrahman, M. Thoriq; Anggriani, Ida; Abi, Yudi Irawan (Universitas Dehasen Bengkulu, 2025)
Business competition in the culinary sector is becoming increasingly fierce, requiring businesses to provide the best experience and service to customers. Dapur Ayek Bengkulu, as one of the local culinary businesses, faces challenges in maintaining customer satisfaction despite providing good facilities and services. Therefore, this study was conducted to assess the extent to which experiential marketing and service quality influence customer satisfaction. The objective of this study is to determine the impact of experiential marketing and service quality on customer satisfaction at Dapur Ayek Kota Bengkulu. The research method used is quantitative research, with the sample consisting of 65 customers of Dapur Ayek Kota Bengkulu. The results of this study indicate that experiential marketing significantly influences customer satisfaction (significance value 0.000). Service quality also significantly influences customer satisfaction (significance value 0.000). Both variables simultaneously significantly influence customer satisfaction (F-test, significance 0.000). The coefficient of determination (R²) value of 0.519 indicates that 51.9% of the variability in customer satisfaction can be explained by experiential marketing and service quality.